The influence of boutique store atmosphere on customer satisfaction, store loyalty and repurchase intention / Bianca van Niekerk - Van Niekerk, Bianca (2016)
The global fashion retail industry has been characterised by fierce competition for numerous years. Boutiques face increasing pressure to distinctly differentiate themselves from competing retail stores offering fashion merchandise, since customers are becoming ever more demanding as fashion evolves and new trends reach South African retail stores. Accordingly, marketers have to ensure customer satisfaction, build store loyalty, and stimulate repurchase intentions in the fashion retail industry in order to survive and prosper. For marketers to attract and retain customers, they have to adjust their marketing strategies and utilise various elements in the marketing mix to compete for customers’ attention, satisfy their retail experience needs, and encourage them to return. Shopping for clothes forms a significant part of many South African females’ lifestyles. Customers to whom fashion is important, have specific needs and wants and desire specific retail experiences. These customers are also becoming increasingly more sophisticated and individualistic, and therefore turn to small, speciality retailers such as boutiques, which they believe can accommodate them by providing unique and tailored retail experiences. Essentially, these customers do not merely purchase the retailer’s merchandise; they want to experience the store atmosphere the retailer offers. Therefore, it is important for boutiques to be aware of their store atmosphere which can offer customers a satisfying, consistent and sound retail experience. Customers who positively experience a retailer’s store atmosphere may feel more satisfied with the boutique, and may return to the retail store in the hope of receiving a similar retail experience. Once the customer returns to the same retail store, the possibility arises that the customer may become store loyal. As soon as the customer keeps on returning to the same retail store, the probability of repurchase intentions becomes real. That said, store atmosphere is considered to be a significant marketing tool, given that it provides boutiques with the power to manipulate a customer’s retail experience which could ultimately influence, customer satisfaction, store loyalty and repurchase intention. The primary objective of this research study is to investigate store atmosphere as a second-order construct model comprised from four sub-dimensions (factors) namely the retail store exterior, interior, layout and design and point-of-purchase and décoration in order to determine the interrelationships between these sub-dimensions (factors), customer satisfaction, store loyalty and repurchase intention in the fashion retail industry. In order to address this, a descriptive research design was followed and self-administered questionnaires were fielded amongst females, 18 years and older with an average monthly household net income of more than R14 000 (medium-to-high household income) who have bought items most recently from boutiques in Potchefstroom and Klerksdorp during the past six months. Judgemental, convenience and quota sampling methods were used to select the sampling units and sampling elements. A total of 361 questionnaires were ultimately analysed. With respect to the empirical results of this research study, respondents agreed the most that the exterior location of the boutique is convenient, the entrance to the boutique is inviting, the interior of the boutique is clean and that the temperature in the boutique is comfortable. Regarding the layout and design of the boutique, respondents agreed the most that the checkout and service points in the boutique are well placed and that all the spaces in the boutique are creatively utilised, as well as that the furnishings in the boutique are attractive. Finally, regarding the point-of-purchase and décoration of the boutique, respondents agreed the most that the pricing of the merchandise in the boutique is clearly visible and that the merchandise is well displayed. All the measurement scales measuring the sub-dimensions (factors) and constructs of this research study exhibit internal consistency reliability as well as content, construct and criterion validity. The standardised model results indicate that all statements included in the measurement model exhibit significant factor loadings above the recommended cut-off point, exhibiting a large effect in all instances, leading to the retention of all statements for further statistical analysis. With respect to the assessment of the structural model, the fit indices indicate an acceptable model fit. Based on the empirical results obtained from this research study, it became clear that store atmosphere has a large direct influence on customer satisfaction and store loyalty, albeit with no direct influence on repurchase intention. Both mediation relationships realised a medium indirect effect between store atmosphere and repurchase intention with customer satisfaction and store loyalty as mediators. The recommendations of this research study mainly focus on strategies to improve the store atmosphere of boutiques, since it positively influences customer satisfaction and store loyalty directly and repurchase intention indirectly. Limitations the researcher encountered were mainly related to budget and time constraints. Recommendations for future research include extending this research study to other Provinces of South Africa in order to determine the status quo in these Provinces and to determine whether statistical significant differences exist between respondents based upon demographic and geographic differences with respect to the constructs of this research study. === MCom (Marketing Management), North-West University, Potchefstroom Campus, 2015